PROSES BERPIKIR MAHASISWA DALAM PEMECAHAN MASALAH APLIKASI INTEGRAL DITINJAU DARI KECEMASAN BELAJAR MATEMATIKA (MATH ANXIETY) - Eka Fitria Ningsih (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2016)
This study aimed to describe : 1) the thinking process of mathematic students with high and low math anxiety in understand the problem â€œintegral applicationâ€; 2) the thinking process of mathematic students with high and low math anxiety in making a plan to solve problems â€œintegral applicationâ€; 3) the thinking process of mathematic students with high and low math anxiety in carry out the plan to solve problems â€œintegral applicationâ€; 4) the thinking process of mathematic students with high and low math anxiety in look back the answer â€œintegral applicationâ€. This type of research was a qualitative research case study method. There are fourth subjects in this research: two students with high math anxiety and two students with low anxiety. Sampling was done by purposive sampling. The data was validated using a time triangulation test. The results of this research showed that (1) when attempting to understand the problem, planning an approach to solving the problem, carry out the planning, look back the answer the students with high math anxiety used convergent thinking process; (2) when attempting to understand the problem, planning an approach to solving the problem, carry out the planning the students with low math anxiety used divergent thinking process while look back the answer used convergent thinking. Keywords : math anxiety, thinking, divergent, convergent